Sex Differences of Microglia and Synapses in the Hippocampal Dentate Gyrus of Adult Mouse Offspring Exposed to Maternal Immune Activation - Hui, Chin Wai; Vecchiarelli, Haley A.; Gervais, Étienne; Luo, Xiao; Michaud, Félix; Scheefhals, Lisa; Bisht, Kanchan; Sharma, Kaushik; Topolnik, Lisa; Tremblay, Marie-Ève (Frontiers in Cellular Neuroscience, 2020)
Schizophrenia is a psychiatric disorder affecting ~1% of humans worldwide. It is earlier and more frequently diagnosed in men than woman, and men display more pronounced negative symptoms together with greater grey matter reductions. Our previous findings utilizing a maternal immune activation (mIA) mouse model of schizophrenia revealed exacerbated anxiety-like behavior and sensorimotor gating deficits in adult male offspring that were associated with increased microglial reactivity and inflammation in the hippocampal dentate gyrus (DG). However, both male and female adult offspring displayed stereotypy and impairment of sociability. We hypothesized that mIA may lead to sex-specific alterations in microglial pruning activity, resulting in abnormal synaptic connectivity in the DG. Using the same mIA model, we show in the current study sex-specific differences in microglia and synapses within the DG of adult offspring. Specifically, microglial levels of cluster of differentiation (CD)68 and CD11b were increased in mIA-exposed females. Sex-specific differences in excitatory and inhibitory synapse densities were also observed following mIA. Additionally, inhibitory synaptic tone was increased in DG granule cells of both males and females, while changes in excitatory synaptic transmission occurred only in females with mIA. These findings suggest that phagocytic and complement pathways may together contribute to a sexual dimorphism in synaptic pruning and neuronal dysfunction in mIA, and may propose sex-specific therapeutic targets to prevent schizophrenia-like behaviors.